Effects of a high-intensity, low-volume overload physical exercise program on metabolic health parameters in sedentary adult women. (Revista horizonte, 2014)
Objective: To determine the metabolic and physical effects of a 12-week high-intensity, low-volume overload exercise program in sedentary working adult women. Methods: A longitudinal experimental study design was used. Forty women between 30 and 60 years of age were randomly assigned to an experimental group (EG; n=20; undergoing a 3-month high-intensity overload exercise program) or a control group (CG; n=20; no physical exercise). Four muscle groups were chosen to be exercised with loads that were given until fatigue was reached. Biochemical profile, body composition and physical condition were measured before and at the end of the experiment. Results: in comparison to GC, GE decreased the plasma contents of basal glucose, total cholesterol, triglycerides, LDL, VLDL. In relation to the functional capacity of the muscle tissue, a variable related to physical condition, the exercise group significantly improved the functional capacity of the four muscle groups evaluated, in addition to a total muscular improvement in comparison to the CG. Conclusions: high intensity and low volume overload training is able to decrease plasma levels of glucose, total cholesterol, triglycerides, LDL and VLDL, and increases the work capacity of muscle tissue. This finding demonstrates that training sessions performed twice a week for 30 min are an effective method in the modification of cardiovascular risk factors in sedentary adult women.